SIFAT PAPAN PARTIKEL DARI CAMPURAN KULIT KAYU Rhizophora apiculata BI DAN Acacia crassicarpa A. Cunn. Ex.Benth BERDASARKAN KONSENTRASI PEREKAT UREA FORMALDEHIDA - Hartati, Rima; Indrayani, Yuliati; Yani, Ahmad (JURNAL HUTAN LESTARI, 2018)
The need of the Indonesian people to wood each year increases with the increase of population. This is not matched by the existing of wood supply, so that another alternative is needed to meet the wood demand by making wood composite such as particle board. The purpose of this research is to evaluate the effect of concentration UF adhesive, material composition and the interaction of both factors on physical and mechanical properties of particle board made from Rhizophora apiculata BI bark and Acacia crassicarpa A.Cunn.exBenth that meet the JIS A 5908-2003 type 8 standard. The materials used in this study are bark of mangrove, bark of acacia, urea formaldehyde adhesive, liquid paraffin and catalyst. Particle board were prepared with the composition of raw materials of bark of mangrove: bark of acacia were 100: 0, 50: 50, 0: 100Â  and adhesive concentration ofÂ  8%, 10%, 12%. Particle board was made with size of 30 cm x 30 cm x 1 cm with target density of 0,6 gr/cm3. Hot pressure was done for 10 minutes with a temperature of 120 oC and pressure of 20 kg/cm2. The results showed that the composition of the material had a significant effect on moisture content, thickness swelling, water absorption, internal bonding, MOR and MOE. The adhesive concentration factor significantly affected the thickness swelling, internal bonding, MOE and MOR. The interaction of both factors had only a significant effect on the screw hold strength, while there is no significant effect on the other physical and mechanical properties. The best physical and mechanical properties are generated by particle board with composition of bark of mangrove and bark of acacia (50:50) and 12% adhesive concentration.Keywords: adhesive concentration, bark of acacia, bark of mangrove, particle board, physical and mechanical properties.